The Performance Evaluation of SMA Spring as Actuator for Gripping Manipulation - Andik Setiawan, Made (Jurnal Teknik Elektro, 2007)
This paper is to present the evaluation of a TiNi Shape Memory Alloy (SMA) spring as actuator for the gripping manipulation. The SMA spring employed was a TiNi tensile spring which has a diameter of 50 mm wire and 350 gram hanging mass. The gripper fabricated consists of two fingers and each finger is actuated by the SMA spring. The total angular displacement of the gripper is 300. The power consumptions, the movements and force generations experimentations have been conducted. The DC signal and PWM signal with 12, 12Hz, 25Hz, 125Hz, 250Hz and the 1150Hz have been employed for driving the SMA. The experimental results indicated that the 125Hz of PWM signal was likely to be had a better performance than the other signals. The 125Hz PWM signal generated faster movement, lower power consumption, and constant rate of force. In this study, closed-loop control for gripping manipulation was also conducted. The close loop controller used is PID controller. The Ziegler-Nichols method has been used to predict the optimal gain of the controller, but the best performance was determined by experimentally tuning of the gains. The experimental results indicated that the PID controller is likely to be reliable controller for gripping manipulation of the SMA spring. To obtain the better performance, it is important to consider the SMA cooling responses and the long time of retain in certain position of the gripper.